Spy : a thriller - Bell, Ted. (New York : Atria Books, 2006)
Things along America's southern border are rapidly reaching the boiling point. American girls are being snatched from their homes, ranches are burning, and armed Mexican troops cross the border at will in support of narcotics smugglers and illegal immigrants. By day, Americans take up arms and plan reprisals. An all-out border war is no longer inconceivable--it's happening! On assignment for the British Secret Service, a man leads a mysterious expedition into the furthest reaches of the Amazon River, where he is captured by indigenous cannibals. Forced into slave labor, he witnesses the unimaginable: golden domes and minarets rise beneath the rainforest canopy. Vast terror armies are being recruited and trained in the jungle. Their goal: a vicious jihad that will unite one continent--and destroy another. They possess weapons only dreamed of by the Western allies. Somehow he must escape his captors and live to tell the tale.--From publisher description.
Maps on lining papers.
Keywords: Hawke, Alex (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Terrorists -- Fiction; Rain forests -- Fiction; Amazon River Region -- Fiction; Suspense fiction